2020
DOI: 10.1093/mnras/staa857
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing the Universe: a comparison between the EAGLE simulations and the nearby DustPedia galaxy sample

Abstract: We compare the spectral energy distributions (SEDs) and inferred physical properties for simulated and observed galaxies at low redshift. We exploit UV-submillimetre mock fluxes of ∼ 7000 z=0 galaxies from the EAGLE suite of cosmological simulations, derived using the radiative transfer code skirt. We compare these to ∼ 800 observed galaxies in the UV-submillimetre range, from the DustPedia sample of nearby galaxies. To derive global properties, we apply the SED fitting code cigale consistently to both data se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 128 publications
(221 reference statements)
2
38
0
Order By: Relevance
“…Finally, it has been suggested that E may underestimate the FUV attenuation (Baes et al 2019). This may be a result of the constant dust-to-metals ratio governing the diffuse dust mass, the modelling of dust in HII regions (Trčka et al 2020), or the global star-dust geometry (e.g. Narayanan et al 2018;Salim & Narayanan 2020).…”
Section: Model Comparisonsmentioning
confidence: 99%
“…Finally, it has been suggested that E may underestimate the FUV attenuation (Baes et al 2019). This may be a result of the constant dust-to-metals ratio governing the diffuse dust mass, the modelling of dust in HII regions (Trčka et al 2020), or the global star-dust geometry (e.g. Narayanan et al 2018;Salim & Narayanan 2020).…”
Section: Model Comparisonsmentioning
confidence: 99%
“…We leave for future work the effect of realistic non-spherical or complex structures, which could be treated by postprocessing simulated galaxies (e.g. Trčka et al 2020;Vogelsberger et al 2020).…”
Section: Galaxy Modelmentioning
confidence: 99%
“…Therefore, as mentioned in Section 2.2, we leave for future work the effect of realistic structures, which could be treated by post-processing simulated galaxies (e.g. Camps et al 2016Camps et al , 2018Trayford et al 2017;Trčka et al 2020;Liang et al 2018;Ma et al 2019;Vogelsberger et al 2020). Note that we realized the desired spatial distribution of dust using discrete particles (Section 2.3).…”
Section: Possible Other Effectsmentioning
confidence: 99%
“…This is an expected behaviour, since the three ratios correlate with each other. Bianchi et al (2018) and Trčka et al (2020) showed a strong correlation of sSFR with f abs and the dust-to-stellar mass ratio, respectively. A correlation between f abs and the dust-to-stellar mass ratio is also expected, since the dust mass and stellar mass are calculated from their respective luminosities.…”
Section: Discussionmentioning
confidence: 94%